Labrador Inuit and their arrow shafts - Mitchell, Greg (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2015)
From the 16th to 18th centuries, Labrador Inuit seem to have valued softwoods (from coniferous tree boles) for the manufacture of arrows and darts used in hunting and warfare. Microscopic examination of Inuit arrow shafts from the Twin Island 3 site (EkBc-07) in Red Bay shows that balsam fir (Abies balsamea) was the preferred species for these purposes in the 16th century. Balsam fir is found in abundance in the inner bays of southern Labrador and was easily accessible to Inuit. However, archival sources indicate that by the 18th century Labrador Inuit desired another species of softwood for arrow and dart shafts, one that grew only on the island of Newfoundland. I propose that the sought-after species was one, or both, of the two pine species growing in central Newfoundland (Pinus strobus or Pinus resinosa). Procurement of pine wood from Newfoundland would add another dimension to the established mobility and trading patterns of Inuit in southern Labrador. Conflicts with Europeans during the 16th through 18th centuries in the Strait of Belle Isle and the Petit Nord (on Newfoundland’s Great Northern Peninsula) may, in part, have been a result of the disruption in these travel and harvesting patterns. I suggest that iron products and wooden shallops (boats) from southern Labrador and northern Newfoundland were not the only “southern” commodities actively sought by Inuit during the early stages of European occupation; central Newfoundland’s pine wood was also important for manufacture of arrow shafts.